2018
DOI: 10.31665/jfb.2018.4160
|View full text |Cite
|
Sign up to set email alerts
|

Do food bioactives play a role in attention-deficit/hyperactivity disorder?

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common diagnosis in children, which may persist into adulthood. Short-term benefits of pharmacological treatment have been shown, but concerns regarding long-term efficacy and safety have led to a search for alternative treatments. Nutrition may be an important factor in psychiatric disorders. At group level, food bioactives do not appear to play a significant pathogenetic or therapeutic role in ADHD. Benefits of treatment with omega-3 fatty acids, vitamins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Furthermore, the findings of several prospective cohort studies have shown that prenatal and early postnatal nutrition are associated with internalizing and externalizing problems in children aged 5-7 years (Jacka et al, 2013;Pina-Camacho et al, 2015;Steenweg-de Graaff et al, 2014). In addition, various vitamins, trace elements and omega-3 fatty acids have been suggested to play a role in child mental disorders (Lange, 2017(Lange, , 2018b(Lange, , 2020aLange et al, 2017). For example, dietary omega-3 PUFA deficiency has been associated with an increase in the risk of several mental disorders in children, such as attention deficit/hyperactivity disorder (ADHD), autism spectrum disorders (ASD) and mood and psychotic disorders (Lange, 2020b(Lange, , 2020c.…”
Section: Food Neuropsychology and Child Mental Disordersmentioning
confidence: 99%
“…Furthermore, the findings of several prospective cohort studies have shown that prenatal and early postnatal nutrition are associated with internalizing and externalizing problems in children aged 5-7 years (Jacka et al, 2013;Pina-Camacho et al, 2015;Steenweg-de Graaff et al, 2014). In addition, various vitamins, trace elements and omega-3 fatty acids have been suggested to play a role in child mental disorders (Lange, 2017(Lange, , 2018b(Lange, , 2020aLange et al, 2017). For example, dietary omega-3 PUFA deficiency has been associated with an increase in the risk of several mental disorders in children, such as attention deficit/hyperactivity disorder (ADHD), autism spectrum disorders (ASD) and mood and psychotic disorders (Lange, 2020b(Lange, , 2020c.…”
Section: Food Neuropsychology and Child Mental Disordersmentioning
confidence: 99%
“…While the etiology of ADHD appears to be multifactorial, definite causes remain unknown. Doubts regarding the effectiveness of commonly used ADHD therapies on clinically relevant outcome measures, the unproven long-term efficacy of treatment and concerns surrounding potentially serious adverse effects of medication have led to a search for alternative treatment options (Lange, 2017;Lange, 2018a;Lange, 2020b), including micro-and macronutrients and diets (Lange, 2018b;Lange, 2018c). Recent findings suggest that the gut microbiome dysbiosis associated with dietary patterns may be linked to a susceptibility to ADHD (Wang et al, 2020).…”
Section: Gut Microbiota In Mental Disordersmentioning
confidence: 99%
“…In short, depression is a clinically and probably pathophysiologically heterogeneous condition. Thus, as in other mental disorders, there is unlikely to be a one-fits-all solution in regard to the therapeutic efficacy of food bioactives such as probiotics (Lange, 2018b;Lange et al 2020). The identification of subgroups of people who are most likely to benefit from probiotic supplementation may therefore be necessary.…”
Section: Table 2 Potential Mechanisms Involved In Probiotic Effects mentioning
confidence: 99%